THE VIABILITY GAP FUNDING (VGF) SCHEME IN CONSTRUCTION ASSIGNMENT LRT JABODEBEK PHASE 2 PROJECT ECONOMIC AND FINANCIAL ANALYSIS - Satriadi, Ery
The development of transportation infrastructure is very necessary for the process of developing connectivity between regions and an effort for regional equity in Indonesia. This necessity doesn’t align with Indonesia’s financial capacity to finance the infrastructure. This gap creates financing innovations between the Government of Indonesia and business entities, such as the Viability Gap Fund. The mobility with a fairly high demand for passengers is the generation from Bogor to Jakarta. Based on BPS (2019), vehicles mobility is 151,057,724 vehicles per year using the Jagorawi toll road to mobilize to Jakarta from Bogor or other suburbs. The high opportunity of passenger generation encourages the Government of Indonesia to plan the construction of LRT Jabodebek Phase 2 and offer this business under the Public-Private Partnership (PPP) scheme. This research used the secondary data from PT. Adhi Karya (Persero) Tbk. Further financial calculation has implemented discounted cash flow method to analysis financial feasibility on LRT Jabodebek Phase 2. Financial feasibility without Government of Indonesia support is economically feasible but not financially feasible. Therefore, project financing support from the Government of Indonesia is required. This project planned with a concession period of 50 years, the financial feasibility calculated through the PPP scheme in the form of VGF funding support (max. 49% total capex) and the maximum tariff applied based on Ministry of Transportation regulations. The result of analysis consisted of NPV 2,255.9 billion rupiah and IRR 10.15% which is higher than the project’s WACC of 9.26%. Therefore the project is financially feasible, although the IRR of the project might be less attractive for some private investors. In order to make this project more attractive to private investors, it is recommended to increase non farebox revenue, and to create concession to build TOD (Transit Oriented Development).